EVALUATION OF OLEANDER PLANTS CONTAMINATION GROWN IN CALCAREOUS SOIL CONTAMINATED WITH SOME HEAVY METALS (NI, CD, PB) ACCORDING TO INTERNATIONAL POLLUTION STANDARDS. - Salih, Dhay Mahdi; Naser, Kadhim Makke (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
A factorial pot experiment was conducted according to a completely randomized design (CRD) in greenhouse to evaluate contamination of oleander plant with some heavy metals, based on calculation of international environmental pollution indicators and effect of heavy metals on growth of oleander plant , with three factors and six replications. soil was treated with three heavy metals: Pb, Cd, and Ni, and four combinations: Pb + Cd, Cd + Ni, Ni + Pb, and Pb + Ni + Cd, with two levels of each element: 0 and 120 for Lead, 0 and 10 for Cadmium, and 0 and 70 mg kg-1 for Nickel with six time periods used for sampling: 40, 80, 120, 160, 200 and 240 days after planting, using sandy loam soil. Treatments symbolized as TNi, TCd, TPb, TCd,Ni, TNi,Pb, TCd,Pb, TCd,Ni,Pb, and TO. Results showed an increase in values of bio concentration factor (BCF) of oleander root system for Ni in TNi, TCd,Ni, TCd,Ni,Pb, and TNi,Pb treatments, reaching 0.9, 0.43, 0.50, and 0.77, respectively, and decreased in the rest treatments. Highest values were for Cd in treatment C, which reached 1.57, while it was less to other treatments. Values are lower from one for, oleander plant is considered one of plants that accumulate Cd. Values of BCF were low for Pb. Values of BCF increased with increasing time periods. Values of the bioaccumulation factor (BAC) increased with increase in concentrations of available heavy metals in soil. Values of biological transfer factor (TF) for Cd, Ni, and Pb decreased below value of one. Heavy metals added to soil significantly affected values of plant heights, and plant dry weight.